GAMBARAN SANITASI KAPAL PENANGKAP IKAN DI DERMAGA 2 PELABUHAN PERIKANAN SAMUDERA (PPS) CILACAP TAHUN 2025 - Erina Adelia; Bayu Suseno; Tri Suryantoro (Unit Penelitian dan Pengabdian Masyarakat Politeknik Banjarnegara, 2025)
Cilacap Ocean Fishing Port (PPS) plays a strategic role in managing fisheries and marine resources. Fishing vessel operations require attention to cleanliness, catch quality, crew health, and the aquatic environment. This study aims to describe the sanitation conditions of fishing vessels and the issuance of sailing health permits. This research is descriptive with a cross-sectional approach. The population includes vessels docked at Pier 2 of PPS Cilacap, using a random sampling technique of 50 ships. Primary data were collected through checklists based on Ministry of Health regulations and questionnaires, while secondary data were obtained from the port authority. The results showed that sanitation aspects meeting standards included the galley (72%), cargo (80%), quarters (52%), potable water (100%), solid waste (80%), standing water (100%), engine room (84%), and medical facilities (100%). However, sewage systems did not meet the requirements. The issuance of the Port Health Quarantine Certificate (PHQC) was 100% in accordance with SOP. In conclusion, ship sanitation and PHQC issuance generally met the assessment standards, except for the liquid waste aspect. These findings are expected to help the port improve sanitation inspections and related educational efforts.